Assessment of physical, chemical, and tribological properties of different biodiesel fuels - Rahman, Md Mofijur; Rasul, Mohammad Golam; Hassan, Nur Md Sayeed; Haji Hassan, Masjuki; Kalam, Md Abul; Mahmudul, Hasan Md (Elsevier Inc., 2017)
Fuel properties of biodiesels are influenced by the physical features of the fatty acid composition, such as the degree of unsaturation, the percentage of saturated fatty acid, monounsaturated fatty acid, and polyunsaturated fatty acid. Fuel properties are the key factors in determining the suitability of any fuel as an alternative fuel. In this study, biodiesels from five different feedstocks have been characterized for their physical and chemical properties. Gas chromatography has been carried out to find out the ester composition of these five biodiesels, and correlation between composition and fuel properties of these five biodiesels have been developed. Fuel properties were measured according to standard procedure ASTM D6751 and EN 14214 and estimated based on the previously published correlation. Also, the quality of these biodiesels was assessed and compared with commercially available biodiesels through multivariate data analysis using PROMETHEE-GAIA software. In the last part, wear and friction of selected biodiesel fuels have been studied and compared with diesel fuel. The result shows that the properties of produced biodiesel are within the acceptable limit of ASTM and EN standards. Highly linear correlations were found between the composition and cetane number, iodine value, oxidation stability, and cold flow plugging point with the regression value of 0.9965, 0.9983, 0.7044, and 0.9985, respectively. Overall, this study found that, among the biodiesels studied, the palm biodiesel was the most suitable alternative followed by the macadamia, moringa, and jatropha, and beauty leaf biodiesel.